2020
DOI: 10.1002/jclp.22931
|View full text |Cite
|
Sign up to set email alerts
|

Patients' interpersonal problems as moderators of depression outcomes in a randomized controlled trial comparing mindfulness‐based cognitive therapy and a group version of the cognitive‐behavioral analysis system of psychotherapy in chronic depression

Abstract: Objectives: Interpersonal problems were examined as moderators of depression outcomes between mindfulnessbased cognitive therapy (MBCT) and cognitive behavioral analysis system of psychotherapy (CBASP) in patients with chronic depression. Methods: Patients received treatment-as-usual and, in addition, were randomized to 8-weeks of MBCT (n = 34) or 8-weeks of CBASP (n = 34). MBCT and CBASP were given in a group format. The Hamilton depression rating scale (HAM-D) was the primary and the Beck Depression Inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
3
0
3
Order By: Relevance
“…If patient assignment could be improved, we expect that drop‐out rates would decrease. For example, a recent study on interpersonal problems indicated that Group‐CBASP should be preferred in persistently depressed patients being non‐assertive, but not in those patients being vindictive or self‐centred (Probst et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…If patient assignment could be improved, we expect that drop‐out rates would decrease. For example, a recent study on interpersonal problems indicated that Group‐CBASP should be preferred in persistently depressed patients being non‐assertive, but not in those patients being vindictive or self‐centred (Probst et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(Schanche et al, 2021) Dalam penelitiannya mengungkapkan bahwa Ketika terjadi kesalahan atau sesuatu berjalan tidak semestinya, orang-orang yang mengikuti MBCT tampak lebih mampu mentolerir kesalahan, mampu untuk mengendalikan kecenderungan untuk mengkritik diri sendiri, tidak terlalu memikirkan kekurangan diri sendiri, serta merasa tidak teralalu pantas untuk dikritik, (Huang et al, 2019) terjadi penurunan skor secara signifikan pada kesedihan (TRIG), emosi negatif (GAD-7 dan Depresi), dan kesulitan pengaturan emosi (DERS) sedangkan tingkat kesadaran (total skor FFMQ) meningkat secara signifikan. (Bang et al, 2023) MBCT secara signifikan penurunan skor pada gejala panik (Probst et al, 2020) memberikan manfaat bagi pasien depresi kronis yang lebih pendendam/ berpusat pada diri sendiri untuk belajar fokus membuat pengalaman baru dengan proses kognitif dan melaksanakan praktek mindfulness. 8 minggu pelatihan sistematis mampu membawa perubahan dalam kebiasaan lama.…”
Section: B Pembahasanunclassified
“…So konnte gezeigt werden, dass Patient*innen in einer CBASP-Behandlung im Vergleich zu denen einer Supportiven Psychotherapie über eine bessere therapeutische Beziehung berichten, die wiederum mit einer stärkeren Abnahme von sozial-vermeidendem Verhalten assoziiert war [22,42].…”
Section: Reduktion Der Interpersonellen Funktionsdefiziteunclassified
“…Diese Analysen beantworten die Frage, ob sich in einer Subgruppe ein besonderer Vorteil zugunsten einer bestimmten Therapie ergibt. [22,42], einer Beobachtungsstudie [3] und einer experimentellen unkontrollierten Studie [28].…”
Section: Bei Wem Wirkt Cbasp Am Besten?unclassified